👤

Supprimer les parenthèses puis réduis chaque expressions:
E= 4x + (5 - 8x)
F= 9,5 + ( - 7x + 8,2)
G= (5x + 4) + ( - 3x - 2)
H= 11,7 ( - 4 + 8x - 9)
K= 5x - (2x - 3)
L= 3x² - (4x² - x + 5)
M=4 + 6x - (- 2x + 7)
N= - 5x - (- 5x² + x - 1)
P= (- 5x + 7) - (8 - 3x) + x
Q= 3x - (- 5 + x) + (- 3x + 3)
R= - 4x² - (2x² - 3x + 1) + (- 2x + 3)
Merci d'avance !!!!


Répondre :

voilà voilà ^^

en espérant t'avoir aider

Voir l'image KINOUETTELOVE
Voir l'image KINOUETTELOVE

Bonjour

E= 4x + (5 - 8x) = 4x + 5-8x = -4x + 5

F= 9,5 + ( - 7x + 8,2) = 9,5 -7x + 8,2 = -7x +17,7

G= (5x + 4) + ( - 3x - 2) = 5x +4 -3x -2 = 2x +2

H= 11,7 ( - 4 + 8x - 9) = 11,7(8x-13) = 93,6x -152,1

K= 5x - (2x - 3)  = 5x-2x+3 = 3x +3

L= 3x² - (4x² - x + 5)= 3x^2 -4x^2 +x -5 =

-x^2 + x -5

M=4 + 6x - (- 2x + 7) = 4+6x +2x -7 = 8x -3

N= - 5x - (- 5x² + x - 1) = -5x + 5x^2 -x +1 = 5x^2 -6x +1

P= (- 5x + 7) - (8 - 3x) + x =-5x -7 -8+3x +x = -x -15

Q= 3x - (- 5 + x) + (- 3x + 3) = 3x +5-x -3x +3 = -x +8

R= - 4x² - (2x² - 3x + 1) + (- 2x + 3) = -4x^2 -2x^2 +3x -1 -2x +3 = -6x^2 +x +2